Evaluation of mandibular incisor extraction treatment outcome in patients with bolton discrepancy using peer assessment rating index. - Sm Safavi; Ah Namazi (Tehran University of Medical Sciences, 2012)
Mandibular incisor extraction in carefully selected cases as an alternative option to four bicuspid extraction or non extraction treatment has been advocated. The purpose of this study was to determine the degree of improvement in occlusion in patients with Bolton discrepancy treated by one lower incisor extraction using Peer Assessment Rating Index (PAR indexes).Pre and post treatment dental casts of 14 patients treated with one lower incisor extraction were included in the study. Pre and post treatment dental casts were scored with PAR index. 70% reduction in PAR index was considered as high standard improvement. To test the hypothesis that the mean improvement in dental occlusion after one mandibular incisor extraction is at least 70%, one-tail one-sample student t-test was used.The mean improvement in dental occlusion in this group of patients was 78%. Fifty percent of the cases finished with a post treatment PAR score of 2. Spearman correlation coefficient was 0.763 (p